An introduction to polymer physics - Bower, David I. (Cambridge University Press, 2002)
Assuming no previous knowledge of polymers, this book provides a general introduction to the physics of solid polymers. Covering a wide range of topics within the field of polymer physics, the book begins with a brief history of the development of synthetic polymers and an overview of the methods of polymerization and processing. In the following chapter, David Bower describes important experimental techniques used in the study of polymers. The main part of the book, however, is devoted to the structure and properties of solid polymers, including blends, copolymers and liquid crystal polymers.